Mothers facing greater environmental adversity experience increased costs of reproduction - Young, Euan A.; Postma, Erik; Lummaa, Virpi; Dugdale, Hannah L. (American Association for the Advancement of Science (AAAS), 2026)
Evolutionary theory of aging predicts that women with increased reproductive effort live shorter lives, but evidence is inconsistent. These inconsistencies could be because environmental conditions influence how much a mother’s life span is reduced when having more children, i.e., their life-span cost of reproduction. Using a structural equation measurement model, we compare how reproductive effort affects the life span of 4684 women exposed across different life stages, or not at all, to the Great Finnish Famine. We find that life-span costs of reproduction became higher in mothers exposed to the famine during reproduction and, for these mothers, amounted to lower life expectancies of ~0.5 years per child. Conversely, reproduction did not shape the life spans of mothers not exposed to the famine or exposed postreproduction or during development. This natural experiment reveals how environmental adversity can influence reproductive costs, providing a biological explanation for previous inconsistent findings while showing how reproductive behavior has shaped the evolution of aging in humans.